Evaluation of Long-term Intensive Care Patients in a Cardiac Surgery Center - Bedih Balkan (Bagcilar Medical Bulletin, 2020)

(untitled)
Objective:This study was aimed to evaluate the clinical and demographic characteristics of patients in a chronic intensive care unit (ICU) in a cardiac surgery center and to research the effect of these characteristics on scoring systems used.Method:From 1 September 2014 to 1 September 2019, the study was performed retrospectively with cases admitted to the chronic ICU due to lengthened intensive care requirements after monitoring in the cardiovascular surgery intensive care or coronary ICU. Each case had study forms including information like age, gender, comorbid diseases, acute physiology and chronic health evaluation 2 (APACHE 2) scores, Glasgow Coma scale, the results were statistically assessed.Results:Two hundred and sixty three patients were enrolled for this study. The mean age of patients was 64.6±6 years, with 61% male and 39% female. Of cases, 46% had coronary bypass surgery (n=122), 25% had valve + aorta dissection (n=67), 19% had acute coronary artery (n=51) and 7% had peripheral artery disease (n=17). The mean follow-up duration for patients was identified as 44.2±96.38 days. Cases developing mortality had significantly higher APACHE 2 scores compared to cases without mortality (p<0.05, 24.9±8.0 vs 20.5±7.2). The most common comorbidities in cases were kidney failure in 41% (n=48). Sixty-nine cases had a percutaneous tracheostomy and 21 cases had a surgical tracheostomy, for a total of 90 cases with a tracheostomy. The mortality rate of entire monitored patients during this study period was 42.6%.Conclusion:Very different problems may be encountered in cases observed in the chronic ICU. For these cases, kidney failure is the most Evaluation of Long-term Intensive Care Patients in a Cardiac Surgery Center